Impacts of Winemaking Methods on Wastewaters and their Treatment - Bories, A.; Sire, Y. (South African Journal of Enology and Viticulture, 2016)
The volume, composition and organic load of wastewaters from five wineries producing white, rosé and red wines by thermovinification, as well as traditionally vinified red wines (75 000 hL to 240 000 hL wine), were studied in terms of the vinification methods used. Liquid-phase vinifications (white, rosé, thermovinification) produce wastewaters rich in sugars: 70% of the chemical oxygen demand (COD) when the must is treated, and flows depend on the daily supply of grapes, representing 40 to 46% of the annual volume of wastewaters during the first month of activity (September). In contrast, solid-phase vinifications do not produce large quantities of waste at harvest, and wastewaters produced mainly during devatting are characterised by a predominance of ethanol (≤ 75% COD) and by staggered flows towards the second month (October), which are less intense (26.7 to 33.6%) and more spread out. The specific pollution coefficients of liquid-phase vinifications (5.18 to 6.04 kg COD/t grapes) are greater than those of solid-phase vinifications (3.82 kg COD/t grapes). The higher the winery’s liquid-phase vinification rate, the more the maximal monthly volume of waste will be intense and early. These results should contribute to the improved design and management of winery wastewater treatments.